Freedom of expression and respect for religious sanctities: Legal Study in International Human Rights Law - Chebbah, Alla (Journal of Human Sciences, 2023)
This article deals with freedom of expression in international conventions and the spaces granted to them, in addition to the intersections that this freedom coincides with the sanctities, rituals and religious symbols, where despite the guarantee of international conventions - all of the Universal Declaration of Human Rights, the European Convention on Human Rights, the American Convention on Human Rights, The African Convention on Human Rights, the Arab Convention on Human Rights - and even the national constitutions for freedom of expression that they impose objective restrictions on them, including not insulting religious symbols, sanctities and rituals and mocking them.